Hot carrier relaxation by extreme electron-LO phonon scattering in GaN - Hess, S; Taylor, R; O'Sullivan, E; Ryan, J; Cain, N; Roberts, V; Roberts, J (1999)
Hot carrier relaxation has been investigated in GaN using non-resonant femtosecond excitation where electrons are excited above and below the LO phonon energy. We observe remarkably rapid electron relaxation; the electron distribution is non-thermal, with a "cut-off" occurring near E-LO. In a preliminary Monte Carlo study we have simulations which reproduce the major experimental observations, confirming the development of a non-thermal electron distribution near E-LO due to the strong electron-LO phonon interaction. Hot phonon effects are pronounced at high carrier densities.